HIGH SCHOOL STUDENTS’ DIFFICULTIES IN ENGLISH SPEAKING SKILLS OF NAMLEA, BURU ISLAND - Ibnu Hajar; Abd. Rahman (Universitas Muhammadiyah Makassar, 2022)
The study aims at exploring the speaking difficulties encountered by high school students and investigating the causes of such difficulties at Namlea , Buru Island The researcher implemented a descriptive qualitative method to describe the speaking difficulties found by high school students at Namlea, Buru Island . The researcher designed an interview to find the data and observed the students speaking. The interview was conducted for each student to investigate speaking difficulties and the causes of such difficulties. The results showed there some difficulties in faced by student in speaking due to some reasons such some students have inadequate English vocabulary, spelling pronunciation, problem. Students are lack grammatical understanding. This research also indicated several factors that cause the students difficulties, such as; Students’ paradigm, motivation, the lack of language environment support, few chances to practice speaking in the learning process.